DEVELOPMENT AND OPTIMIZATION OF MESOPOROUS SILICA NANOPARTICLE LOADED HYDROGEL OF ALLICIN FOR WOUND HEALING - KHERDE, GAURAVI SUNILRAO; KHAIRE, RAHUL DNYANESHWAR; KUNDE, VIKAS DAMU (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this study was to develop and optimize a mesoporous silica nanoparticle (MSN)-loaded hydrogel formulation of allicin to enhance its stability, sustained release, and skin permeation for effective wound healing. Methods: Allicin was characterized through organoleptic, UV, solubility, FTIR, and DSC studies. MCM-41 MSNs were selected as carriers due to superior encapsulation efficiency and solubility enhancement. MSN-loaded hydrogels were formulated using a factorial design and evaluated for physicochemical properties, in vitro release, ex vivo permeation using Franz diffusion cells, and statistical optimization via ANOVA. Drug release kinetics were modeled using Zero-order, First-order, Higuchi, and Korsmeyer–Peppas equations. Accelerated stability studies were performed under ICH conditions for six months. Results: Hydrogel formulations were stable, skin-compatible, and demonstrated uniform drug content (97.68–98.92%). In vitro release showed biphasic profiles with optimized formulations GF7 (94.26±4.18%) and GF5 (93.85±4.06%) achieving maximum release at 12 h. Ex vivo permeation confirmed superior performance of GF7 (95.42±3.65%) and GF5 (94.74±3.45%) with high flux (34.56 and 33.96 µg/cm²/h) and permeability coefficients (1.73×10⁻³ and 1.70×10⁻³ cm/h). ANOVA demonstrated significant influence of Carbopol and propylene glycol, and validation of optimized batch GF5 confirmed high model reliability (desirability 0.980). Release followed first-order kinetics (R² = 0.9789) with anomalous diffusion. Stability studies showed minimal changes in pH, viscosity, spreadability, drug content, and permeation over six months. Conclusion: The MSN-based hydrogel system successfully enhanced allicin’s solubility, stability, sustained release, and skin permeation, offering a promising strategy for topical delivery of unstable phytoconstituents.